فهم آيات الجهاد بين النص والسياق والتاريخ ــ دراسة تحليلية في ضوء مقاصد الشريعة - الحضيري, محمد علي حمزة (مجلة الاصالة, 2025)
فهم آيات الجهاد بين النص والسياق والتاريخ ــ دراسة تحليلية في ضوء مقاصد الشريعة